Ionizable polyol from cottonseed oil for anionic waterborne polyurethane-silanol dispersions. Issue 4 (November 2019) - Gaddam, Sashivinay Kumar; Palanisamy, Aruna
A novel cottonseed oil-based ionizable polyol was introduced as ionic soft segment in waterborne polyurethane dispersion (PUD) synthesis. The ionizable polyol was synthesized by ring opening of epoxidized cottonseed oil (ECSO) with 4-aminobenzoic acid (PABA) and blended with hydroxylated cottonseed oil polyol (HCSO) in different weight ratios to develop a series of mixed polyols having different hydroxyl numbers viz., 146, 130 and 114 mg KOH/g. Three different PUDs were synthesized using the mixed polyols, isophorone diisocyanate, and 3-aminopropyltriethoxysilane. The chemical structure, thermo-mechanical properties, and surface properties of cured PUD films were examined using Fourier-transform infrared spectroscopy (FTIR), Dynamic mechanical thermal analysis (DMTA), universal testing machine (UTM) and contact angle measurements respectively. The effect of Si–O–Si cross-linking network density, which increases with an increase in OH values of the mixed polyol was also investigated. All the PUDs prepared in this study exhibited good storage stability (>4 months), and the average particle sizes of PUDs ranged from 18 to 124 nm. The highest hydroxyl mixed polyol derived PUD film (PUD-35 film) exhibited high thermal stability, mechanical strength; Tg value, water contact angle value, chemical, and abrasion resistance properties due to the extended siloxane cross-link network structure. The introduction of ionizable polyol into the soft segment led to an improvement in hard and soft segment phase mixing of PUDs, and this strategy could enrich the exploration of new synthetic methodologies in the field of bio-based PUD manufacturing.